Foreign Direct Investment in Indian Economy. - Kapoor, Vikas (2007)
Over the past few years, India's inward Foreign Direct investment (FDI) has attracted many scholars interest. The objective of this study is to focus on the impact that Foreign Direct investment has for Indian economic growth and development. It seeks to briefly reveal why there has been a recent surge in FDI and also the factors that prevent India from attracting foreign direct investments. Main determinants of FDI will also be revealed in this paper.